Antibiotic-Induced Alterations of the Gut Microbiota Alter Secondary Bile Acid Production and Allow for Clostridium difficile Spore Germination and Outgrowth in the Large Intestine - Theriot, Casey M.; Bowman, Alison A.; Young, Vincent B. (mSphere, 2016)
Antibiotics alter the gastrointestinal microbiota, allowing for Clostridium difficile infection, which is a significant public health problem. Changes in the structure of the gut microbiota alter the metabolome, specifically the production of secondary bile acids. Specific bile acids are able to initiate C. difficile spore germination and also inhibit C. difficile growth in vitro , although no study to date has defined physiologically relevant bile acids in the gastrointestinal tract. In this study, we define the bile acids C. difficile spores encounter in the small and large intestines before and after various antibiotic treatments. Antibiotics that alter the gut microbiota and deplete secondary bile acid production allow C. difficile colonization, representing a mechanism of colonization resistance. Multiple secondary bile acids in the large intestine were able to inhibit C. difficile spore germination and growth at physiological concentrations and represent new targets to combat C. difficile in the large intestine. It is hypothesized that the depletion of microbial members responsible for converting primary bile acids into secondary bile acids reduces resistance to Clostridium difficile colonization. To date, inhibition of C. difficile growth by secondary bile acids has only been shown in vitro . Using targeted bile acid metabolomics, we sought to define the physiologically relevant concentrations of primary and secondary bile acids present in the murine small and large intestinal tracts and how these impact C. difficile dynamics. We treated mice with a variety of antibiotics to create distinct microbial and metabolic (bile acid) environments and directly tested their ability to support or inhibit C. difficile spore germination and outgrowth ex vivo. Susceptibility to C. difficile in the large intestine was observed only after specific broad-spectrum antibiotic treatment (cefoperazone, clindamycin, and vancomycin) and was accompanied by a significant loss of secondary bile acids (deoxycholate, lithocholate, ursodeoxycholate, hyodeoxycholate, and ω-muricholate). These changes were correlated to the loss of specific microbiota community members, the Lachnospiraceae and Ruminococcaceae families. Additionally, physiological concentrations of secondary bile acids present during C. difficile resistance were able to inhibit spore germination and outgrowth in vitro . Interestingly, we observed that C. difficile spore germination and outgrowth were supported constantly in murine small intestinal content regardless of antibiotic perturbation, suggesting that targeting growth of C. difficile will prove most important for future therapeutics and that antibiotic-related changes are organ specific. Understanding how the gut microbiota regulates bile acids throughout the intestine will aid the development of future therapies for C. difficile infection and other metabolically relevant disorders such as obesity and diabetes. IMPORTANCE Antibiotics alter the gastrointestinal microbiota, allowing for Clostridium difficile infection, which is a significant public health problem. Changes in the structure of the gut microbiota alter the metabolome, specifically the production of secondary bile acids. Specific bile acids are able to initiate C. difficile spore germination and also inhibit C. difficile growth in vitro , although no study to date has defined physiologically relevant bile acids in the gastrointestinal tract. In this study, we define the bile acids C. difficile spores encounter in the small and large intestines before and after various antibiotic treatments. Antibiotics that alter the gut microbiota and deplete secondary bile acid production allow C. difficile colonization, representing a mechanism of colonization resistance. Multiple secondary bile acids in the large intestine were able to inhibit C. difficile spore germination and growth at physiological concentrations and represent new targets to combat C. difficile in the large intestine.